Circular economy framework for managing pharmaceutical waste in Malaysia - Lim, Shi Hao (2023)
The main aim of this study was to develop a circular economy framework for managing pharmaceutical waste by proposing a consumer-centric process innovation model in Malaysia. This study explored policies on waste management and interviews were carried out among consumers, a community pharmacist, a pharmacist from the Ministry of Health and a pharmacist with a local pharmaceutical company manufacturer to understand the perspectives of these various stakeholders on pharmaceutical waste management from reverse supply chain point of view.